Censorship detected in GB (United Kingdom) - Voidly (Voidly Global Censorship Index, 2025)
CRITICAL severity censorship detected in United Kingdom. Data sourced from CensoredPlanet.
Censorship Incident ID: GB-2025-0001. Severity: critical. Confidence: 75%